Penguatan peran ayah dalam pengasuhan anak: Mempersiapkan generasi penerus melalui pengasuhan berkualitas - Sukron, Muhammad Ikbal Wahyu; Maulana, Herdiyan; Wijayanti, Fauziah; Anugrah, Nazir Ultama (Universitas Negeri Jakarta, 2025)
Father involvement in early childhood is a critical determinant of children’s cognitive development, emotional stability, social competence, and academic achievement. In Indonesia, however, fathers’ participation in parenting remains relatively low, influenced by cultural norms, gender expectations, and work-related demands. This community service program, implemented at TK Aisyiyah Bustanul Athfal 23 GDC in Depok, sought to strengthen father involvement through a community-based workshop approach. The program featured interactive sessions, experience sharing, and role-play activities aimed at enhancing fathers’ parenting knowledge and skills. Core topics included effective communication, bonding activities, and strategies for balancing work and family responsibilities. Participants reported gaining valuable insights and practical tools to support their roles as emotionally and socially responsive caregivers. Overall, this initiative underscores the importance of redefining fatherhood in contemporary Indonesian families and contributes to the broader vision of cultivating a strong, character-driven generation in preparation for Indonesia Emas 2045.